Global regulation of foreign direct investment - Seid, Sherif H. (Aldershot, Hampshire, England ; Burlington, VT : Ashgate, 2002)
This title analyzes the pros and cons of various positions taken with regard to a global investment agreement to regulate foreign direct investment. It then uses them as a basis for forging a hybrid model called "Regulated Openness".
Includes bibliographical references (p. 231-247) and index.
aia 2/8/16
Keywords: Investments, Foreign; Foreign trade regulation; Investments, Foreign--Law and legislation